Wine consumers' reaction to prices, organic production and origins at the point of sale: an analysis of household panel data. Issue 3 (5th June 2020) - Schäufele, Isabel; Hamm, Ulrich
Abstract: Price premiums are considered as major purchase barriers for organic products and therefore may prevent organic market growth. For wine, however, prices take a double and conflicting effect: they also serve as quality signal for consumers. Therefore, it is of high relevance to examine if price is a major barrier for organic wine as well. Even though many studies already examined price behavior for organic wine through surveys and experiments, it is still to be clarified how consumers' react to price changes in a real market context. So far, no study analyzed consumer preferences for organic labeled wine in daily shopping situations. Through the analysis of the GfK household panel—a high-frequency data set of extensive population coverage—implications for price setting and price promotions in different market segments can be given. In contrast to previous studies, consumers' overall price sensitivity was found to be low for organic wine and consumers' preferred organic over conventional wine. The effect of price as quality cue or purchase barrier and the effect of an organic label on consumers' behavior varied between price categories. Organic wine was valued highest in the low-price category, whereas no price premium for the organic label was examined in the high-price segment. Price sensitivity was extremely high for organic wine in the low-price segment, while price functioned as quality signal in the premium segment for organic and conventional wine similarly. This study verified previous stated preference studies on organic wine through the analysis of actual purchase data. Moreover, new insights for price setting in different price categories were generated through the examination of a large amount of disaggregated data on single consumer purchases.